2007
DOI: 10.1007/s11552-007-9080-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Locked Volar Plating Versus Pinning and External Fixation in the Treatment of Unstable Intraarticular Distal Radius Fractures

Abstract: Introduction We retrospectively compared the outcomes of open reduction and internal fixation (ORIF) with volar locking plate versus standard external fixation and percutaneous pinning in treating similar unstable distal radius fractures with a minimum 2-year follow-up. Methods The ORIF group included 41 patients with an average follow-up of 29 months. The external fixation group comprised 14 patients with an average follow-up of 33 months. Average age at presentation was 45 years in the external fixation grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 37 publications
5
49
0
Order By: Relevance
“…They also concluded that volar locked plating is a boon for unstable fractures because of its stiffer construct and lower rates of complications. 20,21 No complications pertaining to extensor tendons was observed in this study. Similar conclusion was reached in separate studies by Hakim et al and Othman.…”
Section: Discussionmentioning
confidence: 55%
“…They also concluded that volar locked plating is a boon for unstable fractures because of its stiffer construct and lower rates of complications. 20,21 No complications pertaining to extensor tendons was observed in this study. Similar conclusion was reached in separate studies by Hakim et al and Othman.…”
Section: Discussionmentioning
confidence: 55%
“…20 There is extensive work to show that locked volar plates are well tolerated, allow early movement and maintain position even for intraarticular fractures. 21,22 Proposed advantages of locked volar plating include improved pull out strength even in osteoporotic bone. 23 Internal fixation using a dorsal plate, which is greatly advocated, achieves anatomical reduction with good stability.…”
Section: Discussionmentioning
confidence: 99%
“…Rizzo, B.A Katti, J.T. Carotheres [5] in their study had an average of 69 In this study functional outcome is graded using Modified Gartland & Werley [2] wrist grading system. In which excellent are 16.67%, good are 50%, fair are 23.33% and poor are 10%.…”
Section: Discussionmentioning
confidence: 96%